Pengaruh Elastisitas Harga terhadap Permintaan Beras di Pasar Ploso Jombang - Nico Dwi Habbiburahman; Dwi Wahyuni (YASIN, 2026)
Rice is a strategic food commodity whose price fluctuations may affect consumer purchasing behavior. However, as a staple food, demand for rice tends to remain stable despite price changes in the market. This study aims to analyze the effect of price elasticity on rice demand at Ploso Traditional Market, Jombang Regency. This study used a quantitative approach with a descriptive design. Data were collected from 100 consumers through questionnaires, observation, and interviews. Data analysis was conducted using descriptive statistics, normality testing, linearity testing, simple linear regression, and t-tests. The results showed that price elasticity had a positive and significant effect on rice demand, as indicated by a regression coefficient of 1.089 and a significance value of 0.000. Nevertheless, rice demand still showed an inelastic tendency because consumers continued to purchase rice despite price changes. The conclusion of this study confirms that price changes affect rice demand, but the level of consumer response is relatively low because rice is a basic household necessity. This finding contributes to strengthening the study of consumer behavior toward staple food commodities and provides practical implications for the government and market stakeholders in formulating food price stabilization policies and maintaining household food security.